Application of the Discussion Method to Improve Science Learning Outcomes in SD Negeri Rejosari Students - Tri Wahyono (Universitas Sebelas Maret, 2022)
This report is made to improve the learning process that has not been optimal. The research aims to find out how the process of applying the discussion method in improving the learning outcomes of class VI students at SD N Rejosari. This research is a classroom action research with two cycles. In the initial study the concentration of students was still very low so that it had an impact on the results of the scores achieved by students. After the research was carried out, the first cycle obtained an average of 70.46. After the teacher corrected the deficiencies that occurred in cycle II, the average results achieved by students increased. This can be seen from the average score achieved by students, namely 81. It can be concluded that the discussion method can improve student learning outcomes at SD Negeri Rejosari, Surakarta City.